Necrotizing Enterocolitis: LPS/TLR4-Induced Crosstalk Between Canonical TGF-β/Wnt/β-Catenin Pathways and PPARγ - Alexia Gomart; Alexandre Vallée; Yves Lecarpentier (Frontiers Media S.A., 2021)
Necrotizing enterocolitis (NEC) represents one of the major causes of morbidity and mortality in premature infants. Several recent studies, however, have contributed to a better understanding of the pathophysiology of this dreadful disease. Numerous intracellular pathways play a key role in NEC, namely: bacterial lipopolysaccharide (LPS), LPS toll-like receptor 4 (TLR4), canonical Wnt/β-catenin signaling and PPARγ. In a large number of pathologies, canonical Wnt/β-catenin signaling and PPARγ operate in opposition to one another, so that when one of the two pathways is overexpressed the other is downregulated and vice-versa. In NEC, activation of TLR4 by LPS leads to downregulation of the canonical Wnt/β-catenin signaling and upregulation of PPARγ. This review aims to shed light on the complex intracellular mechanisms involved in this pathophysiological profile by examining additional pathways such as the GSK-3β, NF-κB, TGF-β/Smads, and PI3K-Akt pathways.